Analysis of the association between cholinesterase and in-hospital mortality in children with bloodstream infections in the pediatric intensive care unit - Ding, Zuoxu; Sun, Zijiu; Zhong, Qi (Frontiers in Pediatrics, 2025)
ObjectiveOur aim was to assess the relationship between BChE levels on admission to the intensive care unit and death from bloodstream infections in the pediatric intensive care unit (PICU).MethodsWe conducted a retrospective analysis using the Pediatric Intensive Care Unit Database (a large Chinese paediatric intensive care database from 2010 to 2018) to assess BChE levels at the time of intensive care unit admission in 329 critically ill children with bloodstream infection admitted to the intensive care unit. We analyzed the relationship between BChE and death from bloodstream infections. We used multifactor logistic analysis regression and adjusted smooth spline plots to estimate the relationship between BChE and death from bloodstream infections.ResultsOf 329 children, 53 (16%) died in hospital. After correction for confounders, BChE was negatively associated with the risk of death in the PICU. For every 1,000 U/L increase in BChE, the risk of death was reduced by 16% (corrected OR = 0.84, 95% CI: 0.79, 0.89). After adjusting for confounders, the risk of death decreased by 23% for every 1,000 U/L increase in BChE (OR = 0.77, 95% CI: 0.63, 0.96). Patients with BChE levels between 5,000 and 8,000 U/L had a 51% lower risk of death, while those with BChE levels >8,000 U/L had a 77% lower risk of death, compared with those with BChE levels <5,000 U/L.ConclusionAccording to multiple regression analysis, decreased BChE is an independent risk factor for all-cause mortality in children with bloodstream infections in pediatric intensive care units.